Report on the 2023 review and 2024 activity planning workshop of the CGIAR initiative on agroecology project - Ouattara, Songdah Désiré; Orounladji, Michel; Sib, Ollo (2024)
To take stock of the activities carried out in 2023 and validate the 2024 program with stakeholders, the coordination team decided to organize a workshop with all ALL-BF stakeholders. This took place on 17 and 18 April 2024 at CIRDES (Centre International de Recherche Développement sur l'Élevage en zone Subhumide). The workshop was attended by 78 participants, including all the researchers involved in the implementation of the project as well as stakeholders of the Agricultural Living Landscape. The Initiative on Agroecology (Transformational Agroecology across Food, Land, and Water Systems) is a CGIAR research initiative committed to meeting the challenge of sustainable development by 2030. The aim of this initiative is to demonstrate the practicality of agroecology and to promote its adoption by stakeholders in the food system, particularly farmers with small holdings in low-income countries. The initiative works with farmers and other food system stakeholders to ensure that agriculture harnesses nature's goods and services while minimising negative environmental impacts and improving knowledge co-creation and inclusive relationships among those stakeholders. It supports the application of agroecological principles in food, land and water management systems, working towards the codevelopment and implementation of agroecological innovations throughout the food system. To facilitate co-learning and co-development, the Initiative on Agroecology is establishing an international network of Agroecological Living Landscapes (ALL). This initiative is structured around five Work Packages (WPs) whose activities are implemented by a coordinator and a team of researchers in each ALL. The CGIAR Initiative on Agroecology implementation steering team includes members of several CGIAR centres and alliances (Alliance of Biodiversity International and CIAT, IWMI, IFPRI, CIMMYT, CIP, WorldFish and IITA), as well as international partners (CIRAD and CIFOR-ICRAF) and national partners in each country (Burkina Faso, India, Kenya, Laos, Peru, Senegal, Tunisia, Zimbabwe). In Burkina Faso, the Initiative on Agroecology is led by the CIRAD and its partners, the CIRDES and the INERA. In March 2023, the Burkina Faso Agroecological Living Landscape (ALL-BF) was set up in the Hauts Bassins region of Western Burkina Faso, which is the ALL implementation area. The ALL-BF currently includes dairy farmers, collectors affiliated to milk collection centres, private collectors, dairy processing units, government support services (local departments of the Ministry in charge of livestock, farming research, technological research) and private providers (livestock feed suppliers, artificial insemination service providers, microfinance institutions). A number of activities were carried out over the course of 2023 in connection with all the WPs of the Initiative on Agroecology project around the ALL-BF. So as to take stock of the activities carried out in 2023 and validate the 2024 programme with stakeholders, the coordination team decided to organise a workshop with all ALL-BF stakeholders. This took place on 17 and 18 April 2024 in the training room of the CIRDES (Centre International de RechercheDéveloppement sur l'Élevage en zone Subhumide). The workshop was attended by 78 participants, including all the researchers involved in the implementation of the project as well as ALL-BF stakeholders (see attached attendance list).